1-Year outcome of concomitant intracarpal lesions in patients with dislocated distal radial fractures: a systematic assessment of 78 distal radial fractures - Gologan, Renata; Obertacke, Udo; Schreiner, Ute (Archives of orthopaedic and trauma surgery, 2016)
Introduction: Ligamentous lesions are concomitant to dislocated distal radius fractures in a high percentage. The purpose of this study was to evaluate the relevance of intracarpal lesions. Methods: Seventy eight of an original cohort of 104 distal radius fractures (74 %) were studied over a follow-up period of one year after surgery with complete data (X-rays, CT, MRI, follow-up X-rays and questionnaire). Results: Most of our radius fractures (AO 23 type: A 39, B 9, C 30) present additional lesions: 97 %. One-year evaluation showed an average Castaing score of 4.5 ± 2.5 points, means a “good” result of a scale of 0-27. Fifty five of seventy eight had an “excellent” or “good” result (<6 points). No patient had more than 12 points (“fair”). Conclusions: The dislocated distal radial fracture implies severe and complex injury to the whole wrist, mostly concerning intracarpal concomitant lesions (MRI). Surgical therapy of dislocated radius fractures followed by 6 weeks relief through thermoplastic splint seems to be sufficient to achieve good 1-year results. MRI-detectable carpal lesions at the time of the radial fracture are common, but only a few of them seem to decompensate later, give symptoms and became of therapeutic relevance.
Gesehen am 22.02.2019
Published online: 30 November 2015